Obstretas y Pediatras: Experiencia con la Lactancia Materna en sus Programas de Residencia - Meaux-Pereda, Laura; Dávila-Torres, René R.; Parrilla-Rodríguez, Ana M.; Avilés-Pérez, Joanna (Puerto Rico Health Sciences Journal, 2014)
see manuscript